Graduation Ceremony 2001 - Part 2
Recording of the CEU Graduation Ceremony of the class of 2000/2001. After the brief musical interlude, the ceremony continues with the words of the Alumni Speaker and the Student Speaker. The ceremony then continues with the conferring of the master degrees by the Heads of the Academic Departments and CEU Programs.